24-Methylenecycloartanol Isolated from The Fruit Peel of Matoa (Pometia pinnata) and Its Activity as an Antibacterial against Staphylococcus aureus and Escherichia coli - Anwar, Risyandi; Arnov, Steffi Triany; Putri, Ghesta Alifka; Sinaga, Siska Elisahbet; Naini, Al Arofatus; Supratman, Unang (Chimica et Natura Acta, 2024)
Triterpenoids are compounds with highly diverse chemical structures and exhibit interesting biological activities such as antiviral, antibacterial, anti-inflammatory, and anticancer properties. The matoa plant (Pometia pinnata), belonging to the genus Pometia from the family Sapindaceae, has been used in traditional medicine and shows potential as an antibacterial agent. The purpose of this research was to isolate and determine the chemical structure of triterpenoids from the peel of the matoa fruit (P. pinnata) and to evaluate their antibacterial activity against Staphylococcus aureus and Escherichia coli. The ethyl acetate extract from the peel of P. pinnata demonstrated significant antibacterial activity. In this study, a triterpenoid compound was identified, and its chemical structure was determined using spectroscopic methods, including UV, IR, MS, 1H-NMR, 13C-NMR, and 2D-NMR, as well as by comparing data from the literature. The compound was identified as a cycloartane-type triterpenoid known as 24-methylenecycloartanol. The compound was then tested for antibacterial activity against S. aureus and E. coli. The test results showed a minimum inhibitory concentration (MIC) of 500 μg/mL for both bacteria, which was categorized as very weak